Utilizing the global positioning system for cultural heritage mediation and education - Nirnbergová, Veronika (Noria Investigación Educativa, 2023)
The article explores the various digital possibilities through which cultural heritage and other educational content can be effectively conveyed in the curriculum. The functionality of the Global Positioning System in facilitating an interactive guide will be clarified. Additionally, the focus will be on the WhereIGo application builder, an innovative tool that provides a wide range of options for developing unique activities for learners or visitors. These activities encompass the provision of location-specific information and visuals, navigation to subsequent points of interest as well as the inclusion of tasks accompanied by immediate feedback, hints and more. This text primarily centers around the creation of an immersive outdoor guide created for smartphones and designed directly into the educational environment. The village of Věrovany in the Olomouc Region (Czech Republic) serves as the backdrop for this guide. While presenting the output, the process of its development will be addressed, too.